Estimating SARS-CoV-2 exposure in asymptomatic hospitalized children with cancer in Western Kenya: A retrospective analysis of serological data - Katarina M. DiLillo; Catherine S. Forconi; Angela Matta; Jeni Melo; Ryan P. McNamara; Ronald Tonui; Festus N’juguna; Juliana A. Otieno; Boaz Odwar; Ann Kinyua; Douglas A. Lauffenburger; Ann M. Moormann (PLoS ONE, 2026)
Background During the COVID-19 pandemic, concerns emerged that hospital-based care could increase the risk of SARS-CoV-2 infection among pediatric patients with cancer, especially in resource-limited settings where the capacity to isolate patients would be challenging. Yet, infection rates in this population remain poorly documented, and it is unclear whether prior common human coronavirus (HCoV) exposures influence SARS-CoV-2 antibody responses. Here, we used serology to estimate SARS-CoV-2 exposure in children with and without cancer from Western Kenya and evaluated responses to common HCoVs to explore cross-reactivity. Methods We performed multiplex antibody profiling to assess SARS-CoV-2 and HCoV-specific responses in plasma from children with and without cancer sampled between 2014 and 2022. Unsupervised clustering identified participants with elevated SARS-CoV-2 seroreactivity relative to pre-pandemic samples. Seropositivity was further defined using a multi-antigen approach based on IgG levels to nucleocapsid and receptor-binding domain antigens to improve specificity. Cross-reactivity and cross-boosting by common HCoVs were evaluated through correlation analyses and groupwise comparisons of antibody levels, respectively. Results Of 564 children, 474 were healthy (184 pre-pandemic; 290 post-pandemic) and 90 had cancer (16 pre-pandemic; 74 post-pandemic). Post-pandemic, 69% (200) of healthy controls exhibited elevated SARS-CoV-2 seroreactivity, with 51% (148) meeting the criteria for seropositivity. Children with cancer showed similar rates of seroreactivity (67%) and seropositivity (57%) after adjusting for sampling year, with incidence increasing annually from 2020 to 2022. Pre-pandemic samples exhibited weak cross-reactivity to HCoV-OC43 which increased following SARS-CoV-2 infection; however, no significant boosting of HCoV antibodies was observed. Conclusions These findings indicate widespread SARS-CoV-2 exposure among children in Western Kenya and provide no evidence that hospitalization heightened infection risk for pediatric patients with cancer.